Historical Hospitality in the Context of the Desacralisation of Religious Buildings : A Case Study of Poland - Kacper ROSA; Krzysztof SALA (Communications of International Proceedings, 2026)
Accommodation facilities located in historic castles and palaces are characterised by their architectural uniqueness and the distinctive experiential value for guests. Among historic hotels, a particularly noteworthy group is those established in former religious buildings, including churches and monasteries. Such facilities emerge as a result of the secularisation and adaptive reuse of sacred architecture. The aim of this study is to identify economic and non-economic factors influencing the development of the post-sacral hotel sector in Poland. The research hypothesis assumes that the development of post-sacral hotels in Poland reflects hoteliers’ efforts to adapt tourism products to the purchasing behaviour, expectations and preferences of contemporary tourists. The study employs a methodology based on the analysis of secondary data, a review of relevant academic literature and qualitative research. The qualitative component included interviews with selected managers and owners of private hotel facilities located in different regions of Poland. Additionally, customer reviews published on the Booking.com platform were analysed in order to identify users’ perceptions and evaluations of post-sacral hotel facilities. The findings confirm the research hypothesis and indicate that the development of such hotels is driven by increasing customer demand for individualisation, exclusivity and intimate forms of accommodation, as well as by hotel owners’ willingness to preserve and repurpose former religious buildings.
Keywords: post-sacral hospitality; desacralisation; heritage hotels; adaptive reuse; religious buildings.